Bloodstream infections due to Peptoniphilus spp.: report of 15 cases. (14th June 2014) - Brown, K.; Church, D.; Lynch, T.; Gregson, D.; Raoult, D.
Abstract Peptoniphilus spp. are Gram‐positive anaerobic cocci (GPAC) that were formerly classified in the genus Peptostreptococcus. This study describes 15 cases of Peptoniphilus spp. bloodstream infection (BSI) diagnosed from 2007 to 2011 using 16S rDNA sequencing in patients with pneumonia, pre‐term delivery, soft tissue infection or colon or bladder disease. Seven out of 15 (47%) of these cases had polymicrobial BSIs. One of the isolates was closely related to P. duerdenii (EU526290), while the other 14 isolates were most closely related to a Peptoniphilus sp. reference strain (ATCC 29743) and P. hareii (Y07839). Peptoniphilus is a rare but important cause of BSI.